The role of the mother in the moral education of the child - Abu Hamdan, Majed; Saleh, Hala (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study deals with the role that the mother should play in raising her children in a virtuous and benign education in order to provide them with the necessary values that enable them to assume their future responsibilities at all levels. The study deals with many aspects, first: the nature of the role of the mother in the upbringing of her children, second: the general rules used in raising children, the moral needs of childhood, Sixth: Ethical values necessary for raising children healthy education. In conclusion, several proposals were made to contribute to the goal of the study to take advantage of the mother's creative abilities in raising children and to prepare a healthy, moral and moral generation armed with good morals as a way to make a successful future.